Gender Differences in End-Stage Ankle Arthritis. Issue 1 (19th August 2016) - Dodd, Andrew; Pinsker, Ellie; Khan, Ryan M.; Daniels, Timothy R.
Category: Ankle Arthritis Introduction/Purpose: End-stage ankle arthritis (ESAA) is a debilitating disease that does not affect all individuals equally. Gender differences have been identified in patients with end-stage hip and knee arthritis and have stimulated research to explain these findings. The present study was undertaken to examine if gender has a significant effect on pre-operative disability and post- operative outcomes in patients with ESAA. Methods: Patients undergoing ankle arthrodesis (AA) or total ankle replacement (TAR) with minimum 2-year follow-up were identified in the Canadian Orthopedic Foot and Ankle Society prospective ankle reconstruction database. Demographic data, revision data, patient satisfaction questionnaires, and outcome data using the Ankle Osteoarthritis Scale (AOS) and Short-form 36 (SF-36) health survey were collected. Results: TAR: 384 patients were included, with 198 females and 186 males. Preoperatively females had higher rates of pain and disability, demonstrated by lower SF-36 physical component scores (PCS) (31.0 vs 34.5, p < 0.001), and higher AOS pain (54.7 vs 51.1, p=0.05) and AOS disability scores (66.5 vs 59.6, p < 0.001). Postoperatively, both groups had significant improvement in PCS, AOS pain, and AOS disability scores. Females continued to demonstrate lower PCS scores (38.3 vs 41.9, p < 0.001) and higher AOS disability scores (31.0 vs 25.8, p=0.02) than males. Preoperative PCS, gender, age, and arthritis etiology all had a significant impact on postoperative PCS scores, with preoperative PCS scores having the largest impact. Gender had no significant impact on AOS pain and disability scores postoperatively. AA: Results Pending Conclusion: In patients with ESAA, females tend to have higher pre-operative levels of pain and disability compared to males, which persists post-operatively. This is consistent with the hip and knee arthroplasty literature. This finding may be due to females undergoing surgery at more advanced disease states, arthritis etiology, referral bias, or treatment bias. Both males and females have significant and similar degrees of improvement in pain and disability scores after TAR, and reoperation rates and patient satisfaction rates are similar despite the apparent disparity in outcomes.